1989
DOI: 10.4327/jsnfs.42.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anions on binding between calcium and pectic substance.

Abstract: Differences in binding properties between pectic substance and calcium (Ca) in salts or calcium hydroxide were investigated by comparison with the Ca content of pectic substance after treatment with solutions of the above compounds. The pectic substance used for the analysis was prepared in several ways as follows. Pectic substance solution containing 0.1M calcium chloride or 0.1M calcium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, ashed seaweeds were found to show almost the same effect on hardness as Ca(OH)2, though the added amounts were larger. The hardness maintenance effect of Ca(OH)2 results from the strengthening of the tissue structure due to cross linking between Ca and pectic substances (Kaneko et al, 1989 Changes in pectic substances Figure I shows the composition of pectic substances in AIS. Each pectin is shown as the ratio to total pectin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, ashed seaweeds were found to show almost the same effect on hardness as Ca(OH)2, though the added amounts were larger. The hardness maintenance effect of Ca(OH)2 results from the strengthening of the tissue structure due to cross linking between Ca and pectic substances (Kaneko et al, 1989 Changes in pectic substances Figure I shows the composition of pectic substances in AIS. Each pectin is shown as the ratio to total pectin.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, it was found that ume fruit with Ca lactate contained larger amounts of Ca than the fruit without Ca lactate. In a previous paper, we reported that Ca from Ca compounds such as Ca hydroxide, Ca lactate and Ca gluconate combines with pectic substances to form crosslinkages (Kaneko et al, 1989b). Therefore, it is thought that Ca lactate added to solution in which ume fruit was stored would dissociate to Ca ion and lactic acid, and Ca ion would react with pectic substances in the fruit to form cross-linkages.…”
Section: Measurement Of Yeasts and Lactic Acid Bacteriamentioning
confidence: 99%